(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
In the view of heterogeneous flow characteristics of solid particles in pneumatic pipeline system, electrostatic signals of an array 16 electrical charge sensors were developed. The distribution solid particle properties of the electrostatic signals in handling of vertical pneumatic conveying system under different flow conditions were monitored and experimental verification was conducted. The results show that the energy distribution of an array electrostatic signals can be used to determine the distribution of solids inside the pipe. Regardless of the differences in mass flow rate, the pattern of experimental outputs was identical which demonstrates that mass flow rate disparity has no impact on the structure of voltage output. This result also indicates that the electrical charge sensor able to quantify the dissemination of solid particles in pneumatic conveying stably and accurately.